The Power of Art in Breaking Stereotypes of Muslim Women Living in the West: A Feminist Analysis of Rohina Malik's play Unveiled - Al-Khafaji, Dr. Ammar Shamil Kadhim Al-Khafaji (Sulaimani Journal for Humanities, 2026)
Drama and theatre often serve as mirrors that reflect the values, beliefs, and social issues of the societies in which they are produced. The stage is used to explore and comment on contemporary, historical, social and political issues. Through plays, playwrights can critique and comment on societal norms, inequalities, injustices, and power structures. In response to the conventionally passive and limiting portrayals of Arab and Muslim women, some female playwrights such as Rohina Malik created through their solo performances a resistance of such incorrect generalizations. Rohina Malik, the Pakistani American playwright born in 1971, presents a narrative in her play Unveiled (2010) that delves into the lives of five Muslim women immigrants, four residing in the US and one in the UK, highlighting the impact of the September 11th, 2001 terrorist attacks on their lives. The common thread binding these characters is their adoption of the hijab and the shared tradition of serving traditional tea from their native countries during the action of the play. This study explores how Malik's characters confront and overturn common stereotypes, emphasizing the complexity and diversity of their experiences. By focusing on themes such as identity, resilience, and empowerment, the research highlights the significance of narrative in changing public perceptions of Muslim women. The analysis seeks to enrich feminist discourses by demonstrating how the play challenges singular views and encourages a more intricate understanding of the lives of Muslim women in Western societies. Thus, anti-Muslim discrimination in America could be combated with art instead of logical arguments and debate.
Keywords: Stereotypes; Hate crimes; Survival; Violence; Social reform